2014
DOI: 10.3389/fpsyg.2014.01282
|View full text |Cite
|
Sign up to set email alerts
|

Inferring reward prediction errors in patients with schizophrenia: a dynamic reward task for reinforcement learning

Abstract: Abnormalities in the dopamine system have long been implicated in explanations of reinforcement learning and psychosis. The updated reward prediction error (RPE)—a discrepancy between the predicted and actual rewards—is thought to be encoded by dopaminergic neurons. Dysregulation of dopamine systems could alter the appraisal of stimuli and eventually lead to schizophrenia. Accordingly, the measurement of RPE provides a potential behavioral index for the evaluation of brain dopamine activity and psychotic sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…The perseverative behavior (repetition of explorations) was also generally lower in the Wisket animals, which might be due to their lower level of exploratory activity in general. While several studies demonstrated increased perseveration in schizophrenic patients [27][28][29], our data are in agreement with recent human data, which showed decreased repetitive behavior in patients characterized by a dominance of positive psychotic symptoms [30]. As the method is based on the rats' natural tendency to explore their environment, factors such as lack of general exploratory drive and/or the ability to initiate actions (which relate closer to the negative symptoms of schizophrenia than to the cognitive deficits) could affect the investigation of the side-boxes.…”
Section: (Continued On Next Page)supporting
confidence: 93%
See 1 more Smart Citation
“…The perseverative behavior (repetition of explorations) was also generally lower in the Wisket animals, which might be due to their lower level of exploratory activity in general. While several studies demonstrated increased perseveration in schizophrenic patients [27][28][29], our data are in agreement with recent human data, which showed decreased repetitive behavior in patients characterized by a dominance of positive psychotic symptoms [30]. As the method is based on the rats' natural tendency to explore their environment, factors such as lack of general exploratory drive and/or the ability to initiate actions (which relate closer to the negative symptoms of schizophrenia than to the cognitive deficits) could affect the investigation of the side-boxes.…”
Section: (Continued On Next Page)supporting
confidence: 93%
“…The fact that from about the seventh day Wisket rats consumed the same amount of rewards as controls may reflect that the learning impairment was greatly overcome by the repetition of the tasks. Since cognitive training also improves cognitive performance in schizophrenic patients, and it can decrease the chance of acute psychiatric admission, too [13][14][15][16][17][18]30], we suggest the predictive validity of this model in this respect. Several brain structures (e.g.…”
Section: (Continued On Next Page)mentioning
confidence: 85%
“…Reinforcement learning models (Glimcher, 2011;Niv, 2009;Sutton & Barto, 1998) have been used to investigate the process underlying trial-by-trial choices in feedback-based probabilistic learning tasks (e.g., Ahn, Busemeyer, Wagenmakers, & Stout, 2008;Ahn et al, 2014;Li et al, 2014;Liu et al, 2015;Rutledge et al, 2009). These models enable an assessment of the degree to which the participant updates his/her belief in response to feedback.…”
Section: Reinforcement Learning Modelmentioning
confidence: 99%
“…A Greenhouse-Geisser adjustment of degrees of freedom and a Bonferroni correction were used when necessary. To evaluate the strength of the evidence for the differences in the parameters between any two groups, following Fridberg et al (2010) and Li et al (2014), we computed the difference in values of the two posterior distributions in each run obtained from the Bayesian method for each parameter FIGU RE 2 Graphic display of the hybrid reinforcement learning model, in which the nodes represent the variables of interest and the arrows indicate the dependencies among the variables and checked whether the difference distribution was away from zero.…”
Section: Statistics and Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation